1924
DOI: 10.1084/jem.39.6.931
|View full text |Cite
|
Sign up to set email alerts
|

Fat Metabolism in Nephritis

Abstract: It has been known for some time that in some cases of nephritis there is an increase in the blood lipoids, sometimes to the extent of 100 per cent or more above the normal. A review of the literature to 1917 has been given by Bloor (1). Later investigations confirmed these results. Epstein and Rothschild (2) thought the high lipoids in nephritis represented a condition of fat non-utilization. Bloor (1) regarded the abnormalities in blood lipoids in severe nephritis as the result of a retarded assimilation of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1926
1926
1968
1968

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…In a patient with clinical nephrosis, London, Sabella, and Yamasaki (19), using tracer methods, found that the half-life time of her serum cholesterol was prolonged. Moreover, Hiller, Linder, Lundsgaard, and Van Slyke (20) and Ling and Liu (21) showed that in nephrosis the body seemed able to metabolize fats normally, but unable to remove them from the blood. Stanley and Thannhouser (18) administered labelled fat to a nephrotic patient and found a much slower than normal rate of utilization.…”
Section: Discussionmentioning
confidence: 99%
“…In a patient with clinical nephrosis, London, Sabella, and Yamasaki (19), using tracer methods, found that the half-life time of her serum cholesterol was prolonged. Moreover, Hiller, Linder, Lundsgaard, and Van Slyke (20) and Ling and Liu (21) showed that in nephrosis the body seemed able to metabolize fats normally, but unable to remove them from the blood. Stanley and Thannhouser (18) administered labelled fat to a nephrotic patient and found a much slower than normal rate of utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate loads, such as might be eaten in a normal meal, usually cause little or no rise in total lipid concentration of plasma (27) although they are reflected in chylomicronemia and turbidity during the period of absorption (28). To obtain a substantial rise in concentration of plasma fatty acids one must feed a large amount of fat, such as 3.5 Gm.…”
Section: Lipemiamentioning
confidence: 99%
“…There have been reports of reduced removal of fat from the plasma (10,11), but this may merely reflect a relative saturation of the clearing mechanism by the high concentration of endogenous plasma lipids. The lipid clearing effect of an albumin infusion (12) and the demonstration of lipoprotein lipase loss in the urine of nephrotic children (13) suggest that other mechanisms may play a role in the causation of the hyperlipidemia.…”
mentioning
confidence: 99%